Characteristics of Fresh Fruit Bunch Yield and the Physicochemical Qualities of Palm Oil during Storage in North Sumatra, Indonesia - Mohammad Basyuni; Nofrizal Amri; Lollie Agustina Pancawaraswati Putri; Indra Syahputra; Deni Arifiyanto (Indonesian Journal of Chemistry, 2017)
This study examines the fresh fruit bunch (FFB) yield and the effect of fruit storage on the quality of palm oil in Bangun Bandar Estate, Dolok Masihul, North Sumatra, with special reference to the physicochemical parameters. The quality of palm oil is mostly determined by the color, free fatty acids (FFAs), moisture, impurities, carotene content, and deterioration of bleachability index (DOBI). The palm fruits were stored in a refrigerator for 0, 7, 14, 21, and 28 days after harvesting before analyzing their carotenoid content, DOBI, FFAs, moisture, and impurities. The results showed that the potency of the crude palm oil (CPO) types, dura, pisifera, and tenera, were 23.5, 26.2, and 23.6%, respectively. The carotenoid content and DOBI of the palm oil types, dura, pisifera, and tenera, were decreased significantly by lengthy storage of the fruit. By contrast, lengthy storage of the fruit significantly increased the FFA, moisture, and impurity contents of these palm oil types, indicating that this reduced the quality of the palm oil. Oil processed from FFB has excellent quality with a high carotene content and DOBI, and a low concentration of FFA, moisture, and impurities. The present study contributes to palm oil stability and nutritional value.